Influence of facial types on sliding mechanics - Cadenas-Llano María; Castillo-Oyagüe Raquel; Iglesias-Linares Alejandro; Yáñez-Vico Rosa María; Solano Enrique; Torres-Lagares Daniel (Sciendo, 2017)
The present study considered the effect of orthodontic friction in an evaluation of the relationship of craniofacial pattern and surface micro-roughness of fixed appliances as determinants of treatment response and time.